Successful Treatment of a Painful Neuroma Using Fascicular Shifting in the Ulnar Nerve: A Case Report - Hruby, Laura A.; Sporer, Matthias E.; Krusche-Mandl, Irena; Tereshenko, Vlad; Platzgummer, Hannes; Hajdu, Stefan; Aszmann, Oskar C. (Journal of Reconstructive Microsurgery Open, 2023)
Objective We report the case of a 40-year-old man with an inveterate ulnar nerve neuroma following a laceration injury of his left wrist twenty-three years ago. The patient presented with a typical ulnar claw-hand deformity and debilitating neuropathic pain in his hand (VAS 8.4). Pre-operative imaging revealed a neuroma of the ulnar nerve at the Guyon's canal. Moreover, a complete atrophy of all intrinsic hand muscles innervated by the ulnar nerve was present.Methods A Zancolli lasso procedure was performed to reduce the clawing effect. The neuroma was resected producing a nerve defect of five centimeters. Since the injury dated back more than two decades and any motor recovery was deemed impossible at that point, the motor fascicle of the ulnar nerve, i.e. the deep branch, was selectively neurolysed and harvested as an autologous nerve graft. Then the graft was shifted into the defect to be coapted with the superficial branch fascicle in an end-to-end fashion.Results The presented fascicular shift procedure resulted in satisfying and sustained pain reduction. At the six-month follow-up, the VAS decreased to 1.2, and two years post-operatively, the patient reported 2.5 on the VAS.Conclusion The fascicular shift procedure offers an alternative approach to conventional nerve grafts. If nerve grafting is required, using a locally harvested graft avoids additional donor site morbidity. Assuming the clinical scenario allows for fascicular grafting, we strongly suggest considering the fascicular shift procedure as a cost-effective alternative to expensive conduits and processed nerve allografts in sensory nerve reconstruction.
Keywords: neuropathic pain; neuroma treatment; nerve reconstruction